Preliminary studies based on focus groups with public relations professionals and students leading to suggestions for an in-depth study - Ubel, Mary I (Kansas State University, 2007)
The study found, based on a focus group with professionals and secondary research conducted in 2007, that public relations (PR) graduates are not prepared for the job market and that nothing has changed in 15 years to improve this situation. Why? Because there has been no feedback from the professionals, PR students who are hired in PR positions, and PR Students who are not hired in PR positions, to the educators and universities on what is working and what is not working for PR graduates to obtain a position in the PR field. Basically, there is no follow-up after students graduate. This study did preliminary research and developed a survey of PR professionals, PR students and educators so that they can provide feedback. This study made recommendations based on the main points from the focus group, which centered on educational programs, PR students' curriculum, the importance of developing good writing skills, taking business courses, taking several PR internships, being involved in extracurricular activities, and the importance of learning how to prepare a resume. In turn, the follow up survey should help provide security for the PR industry to keep PR alive, by increasing the number of graduates due to their success as a PR professional based on their education.
Keywords: Public relations; Accreditation; Curriculum; Journalism (0391)